Analisis Dampak Body Shaming pada Remaja Perempuan Awal di SMP Negeri 213 Jakarta - Damayanti Damayanti; Desy Safitri; Abdul Haris Fatgehipon (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research was motivated by the rising number of adolescent girls experiencing body shaming, which can lead to negative consequences, particularly affecting their self-confidence. The aim of this study is to explore the impacts felt by female junior high school students after experiencing body shaming. A descriptive method was employed, using questionnaires, interviews, and documentation as data collection techniques. The population of this study consisted of 144 eighth-grade female students at SMP Negeri 213 Jakarta in the 2024/2025 academic year. The sample was selected through purposive sampling, with a total of 50 participants. The data were analyzed using descriptive analysis techniques. The results of the study show that: 1) Body shaming has a significant impact on the four analyzed aspects: global subjective satisfaction, affective distress regarding appearance, cognitive aspects of body image, and behavioral aspects of body shaming. Each aspect shows a negative influence, although the intensity varies. 2) In this study, the cognitive aspect was identified as the most dominant impact, with 38% of respondents categorized as experiencing a high level.